Efeito da luz, temperatura e estresse hídrico no potencial fisiológico de sementes de anis, funcho e endro - Stefanello, Raquel (2005)
The objective of that work was to evaluate the effects of light, of temperature and of hydric stress in the germination and vitality of seeds of anise, fennel and dill. The experiment was led in two stages. In stage I, the seeds were placed to germinate to constant temperatures of 20, 25, 30 ºC and alternate temperatures of 20-30 ºC in the presence and absence of light. The assessed parameters were: germination percentage, first count, index of germination speed, length and dry mass of seedlings. In stage II, the seeds were placed in soaked substratum in polyethylene glicol (PEG 6000) in the osmotic potentials equivalent to zero; -0,05; -0,10; -0,15; - 0,20; -0,25; -0,30 MPa. Germination percentage, first count and index of germination speed were evaluated. In stage I, the procedure employed was reached by chance, with the data submitted to variance analysis and to the Tukey test to a 5% of probability, and in stage II, analysis of polinomial regression was used. According to the results, it is possible to conclude that germination of seeds anise, fennel and dill happen in presence and absence light, however the manifestation of the vigor is favored by light. The germination of dill seeds is larger in light presence. The seeds anise, fennel and dill, without dormancy, germinate better in the constant temperatures of 20 and 25 °C and temperature of 30 °C is not adapted for germination test in these species. The dill seeds are more tolerant to hydric stress than the anise and fennel seeds. The decrease of the osmotic potentials reduces the germination and vigor of seeds anise, fennel and dill, being the most affected vigor than germination. The germination is reduced drastically, starting from -0,1 MPa for fennel and -0,2 MPa for dill, when there is decrease of osmotic potentials with polyethylene glicol 6000.